2009
DOI: 10.1260/1747-9541.4.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A Study of a Successful Experienced Elite Handball Coach's Cognitive Processes in Competition Situations

Abstract: This study explores the cognitive management of a successful experienced elite handball coach during a competition. A coach's activity was examined based on a “single case” by analyzing the content of two types of interviews (semi-structured, stimulated recall) through deductive, then inductive approaches. Results showed: (a) in the planning phase, game plans intended for the competition were elaborated from situations that had long been mastered during training sessions: And (b) in the interactive phase on of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 18 publications
1
34
0
1
Order By: Relevance
“…These results are in line with studies that have shown a home advantage for an animal when its territory is threatened or attacked, even when the defender is smaller than the rival, suggesting an important motivational incentive in territorial defense (Alcock, 1998). Also, these results are consistent with those of Debanne and Fontayne (2009) that carried out a case study with a two-time world champion handball coach, using a videocuing recall-stimulated interview (Lyle, 2003). They highlighted a hierarchical organization of the coach's concerns in which physical involvement is somewhat of a prerequisite before any intervention.…”
Section: Practical Applicationssupporting
confidence: 86%
“…These results are in line with studies that have shown a home advantage for an animal when its territory is threatened or attacked, even when the defender is smaller than the rival, suggesting an important motivational incentive in territorial defense (Alcock, 1998). Also, these results are consistent with those of Debanne and Fontayne (2009) that carried out a case study with a two-time world champion handball coach, using a videocuing recall-stimulated interview (Lyle, 2003). They highlighted a hierarchical organization of the coach's concerns in which physical involvement is somewhat of a prerequisite before any intervention.…”
Section: Practical Applicationssupporting
confidence: 86%
“…To sum up, the decision-making process of handball coaches in relation to using timeouts is multifactorial [4,10,22] and it highlights the coach as strategist of team play. There is no one reason for coaches to use a timeout in handball.…”
Section: Resultsmentioning
confidence: 99%
“…They suggest that teams that took timeouts in the regular phases of games were 1.4x more likely to score in the timeout attack than teams that took timeouts in the last two minutes; and teams that took timeouts with a full team on the court where 1.4x more likely to score in the timeout attack compared to teams that were a man short due to a two-minute suspension. According to Debanne, Angel, & Fontayne [10] this makes sense since handball coaches emphasize a more sound defensive strategy in the later stages of matches. The findings further indicate that using timeouts in positive flow of games can have counter effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations